Religious difference, colonial politics, and Grierson's Linguistic Survey of India. (2nd September 2022) - Majeed, Javed
ABSTRACT: Grierson's Linguistic Survey of India (1903–1928) is one of the most complete sources on South Asian languages. It has influenced all subsequent studies of the language situation in India. However, there are indications in the Survey's volumes, in its unpublished files, and in Grierson's correspondence, that extra-linguistic considerations affected his approach to some Indian languages. Drawing on these sources, this essay focuses on Panjabi, Siraiki, Assamese, and Hindi-Urdu. It shows how factors stemming from Grierson's views on religious difference and on language as a basis for nationality, as well as colonial politics of governance, may have influenced his characterisations of these languages. However, this does not invalidate the Survey, which is not straightforwardly 'colonial'. Moreover, each of these languages is also described using linguistic argumentation, as reflected in the LSI's skeletal grammars and its focus on dialectal variation. As such, we have to work with this tension in the LSI, without trying to resolve it either by rejecting the Survey in toto because of the instances of politics affecting its analyses, or by accepting it wholesale while ignoring the extra-linguistic considerations which influenced how it characterised some Indian languages.